2021
DOI: 10.1096/fj.202001826r
|View full text |Cite
|
Sign up to set email alerts
|

Reduced nicotinamide mononucleotide is a new and potent NAD+precursor in mammalian cells and mice

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri butio n-NonCo mmerc ial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 73 publications
(175 reference statements)
0
44
0
Order By: Relevance
“…A reduced version of NMN is also discussed here as NMNH. Similar to DNR, NMNH also showed much more potency over its oxidized form, by increasing NAD levels faster and by a twofold rise than NMN according to Perez et al 27 The same study showed that NMNH reduced damaged and enhanced healing in renal tubular epithelial cells upon hypoxia/reoxygenation injury. Perez et al also found that NMNH caused a swift escalation in NAD + levels in kidney, liver, muscle, brain, brown adipose tissue, and heart.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…A reduced version of NMN is also discussed here as NMNH. Similar to DNR, NMNH also showed much more potency over its oxidized form, by increasing NAD levels faster and by a twofold rise than NMN according to Perez et al 27 The same study showed that NMNH reduced damaged and enhanced healing in renal tubular epithelial cells upon hypoxia/reoxygenation injury. Perez et al also found that NMNH caused a swift escalation in NAD + levels in kidney, liver, muscle, brain, brown adipose tissue, and heart.…”
Section: Introductionmentioning
confidence: 87%
“…Whereas the DNR molecule can enter the cell and perform NAD synthesis intracellularly where it is converted to NMNH, NADH, and then NAD, the precursor NMNH must first be dephosphorylated extracellularly into DNR before it can enter the cell, and then takes the same intracellular NAD pathway as DNR. 26,27 It has also been demonstrated that NAD levels are not raised through direct absorption of NR or NMN, but that the gut microbiome are converting NR and NMN into a different molecule known as nicotinic acid mononucleotide (NaMN) via deamidation and integration by way of the de novo pathway. 30 The breakdown of NMN into the NAD metabolome caused an increase in metabolites such as nicotinic acid riboside (NaR) and NR.…”
Section: Nicotinamide Riboside (Nr) and Nicotinamide Mononucleotide (Nmn) And Dihydronicotinamide Riboside (Dnr) And Reduced Nicotinamidementioning
confidence: 99%
See 1 more Smart Citation
“…NR can also be produced in bodily tissues starting from its reduced form, NRH, via NRH:quinone oxidoreductase 2 (NQO2), which utilizes NRH as an electron donor [ 19 ]. NRH was shown to be endogenously present in the liver by metabolomic analysis [ 20 ] and it was proposed to come from NADH degradation via NUDIX hydrolases, such as NUDIX5, 12, and 13 [ 21 , 22 ]. Notably, exogenously supplemented NRH can also stimulate NAD production independent of NMRK enzymes, through a mechanism that foresees its phosphorylation to NMNH, the reduced form of NMN, by adenosine kinase followed by the subsequent conversion to NADH and, ultimately, to NAD [ 20 , 23 , 24 ].…”
Section: Nad Biosynthesis In Mammalsmentioning
confidence: 99%
“…Notably, exogenously supplemented NRH can also stimulate NAD production independent of NMRK enzymes, through a mechanism that foresees its phosphorylation to NMNH, the reduced form of NMN, by adenosine kinase followed by the subsequent conversion to NADH and, ultimately, to NAD [ 20 , 23 , 24 ]. NRH and NMNH have indeed been identified as important NAD precursors both in vitro and in vivo [ 22 , 23 , 24 ].…”
Section: Nad Biosynthesis In Mammalsmentioning
confidence: 99%